(untitled) (Лучшие интеллектуальные исследования, 2025)
Abstract: The article presents the development of an autoclave technology for nitric acid leaching of alumina from kaolin clays. The research was motivated by the limitations of conventional agitation leaching, including high nitric acid consumption, significant dissolution of iron impurities, and low aluminum extraction efficiency. Laboratory-scale experiments were conducted using raw, calcined, and enriched kaolin clays in a titanium autoclave under varying temperature, acid concentration, and leaching duration conditions. Calcined non-enriched clay was identified as the most suitable material for autoclave treatment. The optimal parameters—temperature of 200°C, 85–90% acid dosage, and 3-hour leaching time—were validated in a 5-liter setup, achieving up to 87% Al₂O₃ extraction with minimal iron co-dissolution.